Rational Design of a Biocatalyst Based on Immobilized CALB onto Nanostructured SiO2 - Llerena Suster, Carlos Rafael (2023)
The adsorption of the lipase B from Candida antarctica (CALB) over nanostructured SiO2 (Ns SiO2 from now on) with and without the addition of polyols (sorbitol and glycerol) was investigated. The isotherms of adsorption made it possible to establish that the maximum dispersion limit was 0.029 µmol of protein per surface area unit of Ns SiO2 (29.4 mg per 100 mg of support), which was reached in 30 min of exposure. The studies through SDS-PAGE of the immobilization solutions and infrared spectroscopy of the prepared solids determined that CALB (from a commercial extract) is selectively adsorbed, and its secondary structure distribution is thus modified. Its biocatalytic activity was corroborated through the kinetic resolution of rac-ibuprofen. Conversions of up to 70% and 52% enantiomeric excess toward S-ibuprofen in 24 h of reaction at 45 °C were achieved. The biocatalytic performance increased with the increase in protein loading until it leveled off at 0.021 µmol.m−2, reaching 0.6 µmol.min−1. The biocatalyst containing the lipase at the maximum dispersion limit and co-adsorbed polyols presented the best catalytic performance in the kinetic resolution of rac-ibuprofen, an improved thermal resistance (up to 70 °C), and stability under long-term storage (more than 2 years).